Adoption and use of SATO pan for health promotion in Kigali, Rwanda - Theogene, Rutambuka; Wibowo, Kunto Adi (Universitas Padjadjaran, 2024)
Background: The lack of proper sanitation facilities, including toilets, creates a barrier to fulfilling sanitation needs. Rwanda also experiences challenges in sanitation whereby many citizens use traditional toilets. With its innovative design, the SATO Pan toilet has the potential to address the sanitation challenges many communities face. Few studies on SATO Pans have been conducted in some countries. However, among reviewed studies, no research has been identified in Rwanda as the milestone demonstrating the efficiency and quality of the SATO Pan, its impact on sanitation issues, and contribution to improving sanitation and promoting health practices in Kigali City. Purpose: This research aimed to explore the potential factors for the widespread adoption and use of the SATO Pan toilet and to provide a comprehensive analysis of its efficiency and easy use among Rwanda communities in the City of Kigali. Methods: Data were collected using a questionnaire, and 109 respondents were selected based on a purposive sampling technique. The UTAUT 2 Model was used to assess its efficiency and ease of use. The Partial Least Squares-Structural Equation Modelling (PLS-SEMM) method was used for data analysis with the SmartPLS 3. Results: The findings demonstrated that, among the hypotheses tested, Behavioural Intention influences Usage Behaviour, Effort Expectancy significantly influences Behavioural Intention, and Habit significantly influences Behavioural Intention. Conclusion: SATO Pan can considerably improve community sanitation and promote health initiatives through innovative design and use. Implications: The SATO Pan’s adoption and use bring about significant sanitation practices to promote hygiene and health practices. Due to the hygienic and comfortable toilet options, the SATO Pan can often overcome the undesirable effects of traditional open-pit toilets.